2019
DOI: 10.1155/2019/8937427
|View full text |Cite
|
Sign up to set email alerts
|

Luhong Granules Prevent Ventricular Remodelling after Myocardial Infarction by Reducing the Metabolites TMAO and LPS of the Intestinal Flora

Abstract: Background Ventricular remodelling is a common pathological change at all stages of heart disease. Luhong granules are widely used in patients with chronic ventricular remodelling after myocardial infarction and can alleviate chest tightness, shortness of breath, and other symptoms. However, its effect on ventricular remodelling remains to be studied. Purpose In this study, we investigated the effects of these granules on myocardial fibrosis in a rat model of myocardial infarction in vivo. Methods Male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In this study, Bacteroidetes abundance was increased in CF model group mice relative to the control group mice, but the abundance of Bacteroidetes was reduced after AS-IV treatment. This result agreed with the alterations of gut microbiota in the treatment of ventricular remodeling with Chinese herbal medicine ( Yang et al., 2019 ). Strikingly, we found that Akkermansia, Defluviitaleaceae_UCG-011, and Rikenella abundances were markedly increased in ISO-induced CF mice treated with AS-IV, which is consistent with the findings of a published study where drug-administered increased the genus Defluviitaleaceae_UCG-011 in hyperlipidemic rats ( Zhang et al., 2021 ), and in contrast to the outcomes of previous studies where drug-administered decreased the genus Rikenella in high-fat diet mice ( He W. S. et al, 2020 ; Liu J. et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, Bacteroidetes abundance was increased in CF model group mice relative to the control group mice, but the abundance of Bacteroidetes was reduced after AS-IV treatment. This result agreed with the alterations of gut microbiota in the treatment of ventricular remodeling with Chinese herbal medicine ( Yang et al., 2019 ). Strikingly, we found that Akkermansia, Defluviitaleaceae_UCG-011, and Rikenella abundances were markedly increased in ISO-induced CF mice treated with AS-IV, which is consistent with the findings of a published study where drug-administered increased the genus Defluviitaleaceae_UCG-011 in hyperlipidemic rats ( Zhang et al., 2021 ), and in contrast to the outcomes of previous studies where drug-administered decreased the genus Rikenella in high-fat diet mice ( He W. S. et al, 2020 ; Liu J. et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Yang et al (2019) found that oral administration of Luhong granules, a complex mixture of various herb leaves, seeds, roots, flowers, and animal parts, for 6 weeks in acute myocardial infarction-induced Wistar rats could partially reverse ventricular remodeling and improve intestinal barrier function. 152 To note, the serum TMAO and lipopolysaccharides levels in the untreated acute myocardial infarction-induced rats was increased, but the levels of both bacteria-derived products were decreased in the Luhong granules-treated rats. Amplicon sequencing of fecal material of untreated acute myocardial infarction-induced rats showed changes in Desulfovibrionaceae, Escherichia, Akkermansia, Bacteroidales, Alistipes, and Phascolarctobacterium, in which there are potential TMAO producers.…”
Section: Reviewmentioning
confidence: 94%
“…MI surgery was performed as described previously [ 15 ]. The mice were anesthetized and mechanically ventilated using a rodent ventilator.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were isolated from the frozen cardiac tissue, and their concentration was calculated using the bicinchoninic acid (BCA) method (Thermo Fisher Scientific, Waltham, MA, USA; A53225). Immunoblotting was performed as previously described [ 15 ]. In this study, the primary antibodies used recognized NLRP3(1 : 1000, CST, 15101S), Cle-caspase-1 (1 : 1000, Abcam, ab1789515), ASC (1 : 1000, CST, 67824), thioredoxin-interacting protein (TXNIP) (1 : 1000, CST, 14715), caspase-3 (1 : 1000, CST, 9662), BCL-2 apoptosis regulator (Bcl-2) (1 : 1000, CST, 3498), IL-1 β (1 : 1000, Abcam, ab234437), Bax(1 : 1000, Abcam, ab32503), and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (1 : 20000, Proteintech, 60004-1-Ig).…”
Section: Methodsmentioning
confidence: 99%